Diary of a dean - London, Herbert I., 1939-2018 (Hamilton Books, 2010)
Diary of a Dean is a memoir of Herbert London's years at New York University. It follows his personal path from professor and ombudsman to dean of a new "experimental" college. The period in question parallels a tumultuous era in higher education. London's experiences placed him in the eye of the academic hurricane. Although there was considerable debate about the content and nature of higher education in this overheated period, London attempted to maintain a balance between a traditional devotion to the canon of western civilization and emerging technologies and innovations that permit a flex.